Analisis Keberlanjutan Penggunaan Aplikasi Simpati dalam Penanganan Stunting Berbasis Teknologi Digital di Sumedang - Fabialismaya, Deayu Dwi Kania; Hodijah, Alyah; Rahma, Amalia; Mazaya, Betsy Elisse; Taofik, Rehieta Alifia; Sukaesih, Nunung Siti (Universitas Nurul Jadid, 2025)
The handling of stunting in Indonesia continues to develop by utilizing digital technology. Sumedang Regency has implemented the Integrated Stunting Management Information System (SIMPATI) as an innovation in monitoring and preventing stunting through technology. This study is a narrative literature review aimed at analyzing the effectiveness of the SIMPATI application in reducing stunting prevalence. The method used is SWOT analysis of various relevant literature. In its implementation, the SWOT analysis is conducted by identifying the strengths, weaknesses, opportunities, and threats of SIMPATI's implementation based on the data and findings contained in the literature. The research results show that the SIMPATI application provides easy access to real-time data, increases transparency, and supports data-driven policymaking. The implementation of SIMPATI has also contributed to reducing the stunting rate in Sumedang Regency from 32% in 2018 to 8.27% in 2022. However, challenges remain, such as limited internet access in certain areas, inadequate training for healthcare workers, and difficulties in data integration across institutions. Therefore, improvements in digital infrastructure and strengthening user capacity are needed to optimize and sustain the implementation of SIMPATI.